Pengaruh Motivasi Kerja, Kepemimpinan dan Lingkungan Kerja Terhadap Disiplin Kerja Aparatur Sipil Negara (Studi Pada Dinas Sosial Kota Bandung) - Muhamad Fathur Pradana Setitit; Ridho Riadi Akbar (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Employee tardiness data indicate that the level of lateness in January was relatively high, then decreased during March and April as discipline improved. However, from May to August the rate increased again, suggesting that disciplinary problems persisted within the Bandung City Social Service. This inquiry was structured to examine work motivation, leadership, and workplace conditions, and to analyze their relationship with employee discipline in the institution. A quantitative design was applied through a census sampling method involving all seventy-two employees as sample units, although only fifty-eight questionnaires were returned in complete form and used in the analysis. The data were processed with SPSS and interpreted to improve clarity. The findings demonstrate that work motivation exerts a statistically significant positive influence on employee discipline, supported by a t-score of 5.579 and a significance level of 0.00. Leadership demonstrates a positive yet insignificant effect, reflected in a t-score of 0.887 with a significance level of 0.379. The work environment contributes no meaningful effect, indicated by a t-score of –0.012 and a significance level of 0.790. Taken together, the independent variables significantly influence employee discipline, as shown by an overall F-value of 18.991.